A study of facility management operation strategy in shopping malls: Insights from 4 top-class shopping malls in Bangkok. Issue 3 (19th June 2017) - Chotipanich, Sarich; Issarasak, Sittiporn
Abstract : Purpose: This paper is a continuing exploration into facilities management (FM) strategy through the arrangement of its decision choices. The purpose of this paper is to identify the existence of FM operation strategy and to add empirical evidence to this subject to the field of FM and property management. Its main objectives are to gain insights into the arrangement of the FM strategic choices in operation and its relationship with business strategy. Design/methodology/approach: The study investigated the configurations of operational approaches and activities that should reflect strategic decisions. The investigation was undertaken through a study of four reputed shopping malls located in Bangkok. The relevant data were collected through semi-structured interviews with the key FM persons of each case study, plus archival document searches, and observations of operational processes. Subsequently, the data were examined in a cross-case analysis to identify the key patterns of relationships between the FM operational arrangements and the business strategy of the mall. Findings: This study found that the functional scheme of FM adopted in operations was deliberately related to the needs of business strategy and the operations of the given shopping mall. A range of strategic choices for FM operations was also found. Certain choices are shared among the case studies, while their arrangements varied according to the particular business strategy and context. Research limitations/implications: The number of case studies was rather limited, while the results were predominantly involved with a single type of facility. Originality/value: The study identified the pattern of strategic choices entailed in the FM operations in shopping malls. The findings add to the understanding on FM strategy by widening the perspectives about the strategic choices of FM operations and how they are connected with the business strategy and operation model of retail estate. It adds empirical evidence and case studies regarding FM operations and its strategic features.